Quality metrics in coronary artery bypass grafting. (May 2019) - Khan, Faiza M.; Hameed, Irbaz; Milojevic, Milan; Wingo, Matthew; Krieger, Katherine; Girardi, Leonard N.; Prager, Richard L.; Gaudino, Mario
Abstract: Studies on the association between care quality, case volume, and outcomes in coronary artery bypass grafting (CABG) have concluded that consistent adherence to quality measures improves mortality rates and outcomes. However, the quality metrics are not well-defined, and their significance to surgeons and healthcare providers remains uncertain. We review the concept of "quality and quality metrics" and discuss their importance in the context of CABG. Highlights: Quality in CABG has 3 components: structure, process and outcome. Quality in CABG is an all-or-none property. Quality care improves clinical outcomes and lowers readmission rates. Adherence to quality metrics standardizes care and lowers hospital costs.